Indigenous Peoples Social Justice in Management of Coastal Areas - Yono, Dwi; Permadi, Iwan (Law Research Review Quarterly, 2016)
Indigenous peoples have a significant role in the management of coastal areas, in the management of coastal areas based on ecology and local wisdom is part of social justice that involves the State in making laws and regulations in protecting the community in the management of coastal areas and small islands. Indigenous peoples' social justice is related to the government's role in developing coastal areas that neglects the existence of coastal communities, so that the local wisdom of indigenous peoples is marginalized and ignored by the State on the pretext of public interest, while the constitution still provides recognition of the indigenous peoples who are conditional in the State constitution, and its impact is one of them is the existence of Law Number 27 Year 2007 concerning the management of coastal areas and small islands that are ignorant of indigenous peoples revised to Law Number 1 of 2014 concerning amendments to Law No. 27 of 2007 due to the conduct of judicial review in the Constitutional Court due to lack of justice inside it.